2021
DOI: 10.3390/ijms221810063
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Reprogramming in Silica-Induced Lung Macrophages and Silicosis Reversed by Ac-SDKP Treatment

Abstract: Glycolytic reprogramming is an important metabolic feature in the development of pulmonary fibrosis. However, the specific mechanism of glycolysis in silicosis is still not clear. In this study, silicotic models and silica-induced macrophage were used to elucidate the mechanism of glycolysis induced by silica. Expression levels of the key enzymes in glycolysis and macrophage activation indicators were analyzed by Western blot, qRT-PCR, IHC, and IF analyses, and by using a lactate assay kit. We found that silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In addition, it was recently shown that lactate induced the production of reactive oxygen species (ROS) and promoted the expression of UPR genes [ 14 ]. Our previous studies also found that silica induced an increase in extracellular lactate levels in macrophages [ 4 ]. However, it is not clear whether lactate can regulate glycolysis and ER stress in NR8383 macrophages.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In addition, it was recently shown that lactate induced the production of reactive oxygen species (ROS) and promoted the expression of UPR genes [ 14 ]. Our previous studies also found that silica induced an increase in extracellular lactate levels in macrophages [ 4 ]. However, it is not clear whether lactate can regulate glycolysis and ER stress in NR8383 macrophages.…”
Section: Introductionmentioning
confidence: 77%
“…However, some studies have suggested that bone marrow-derived macrophages mainly rely on glycolysis when participating in inflammatory responses, while tissue-resident macrophages mainly rely on oxidative phosphorylation, and glycolysis has been maintained at a low level [ 22 , 23 ]. Our previous study found that tissue-resident macrophages also mainly rely on glycolysis for the production of energy to perform biological functions [ 4 ]. We observed that glycolysis contributed to the regulation of macrophages in silicosis by promoting the activation of M1/M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations